2010
DOI: 10.1080/01609513.2010.503385
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Canada's Drug Prevention Strategy and Creating a Meaningful Dialogue with Urban Aboriginal Youth

Abstract: This article describes some of the risks and challenges faced by Aboriginal youth living in Canadian cities. It evaluates four current drug prevention/education programs for this group and other at-risk youth. The lessons learned from these strategies lead to a proposal for a reflective education approach directed toward opening meaningful dialogue about drugs and alcohol with urbanAboriginal youths in group settings. The objectives of the approach are to create an open dialogue with youths, enhance problemsol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Sharing circles are safe spaces for democratic equal exchange opportunities that play a significant role in the process of healing and are defined by a set of protocols. A guiding rule is one person speaks while others listen, travelling around the circle, sharing one by one (Ghelani, 2010). The team used this strategy when the pause in dialogue seemed unwavering during data collection.…”
Section: Process Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharing circles are safe spaces for democratic equal exchange opportunities that play a significant role in the process of healing and are defined by a set of protocols. A guiding rule is one person speaks while others listen, travelling around the circle, sharing one by one (Ghelani, 2010). The team used this strategy when the pause in dialogue seemed unwavering during data collection.…”
Section: Process Considerationsmentioning
confidence: 99%
“…Despite the study reported in this article focusing exclusively on a baraza – a traditional East African conversational space – in the Kenyan context, several countries have similar indigenous social processes and spaces for dialogue. These lend themselves to culturally responsive adaptations that can increase engagement in research and as a result enable pathways for change that are driven by community members (Balay-As, 2019; Barnes, 2010; Ghelani, 2010; Green and Waiti, 2014, Vanner C. 2015). Kenya and Tanzania both employ mabaraza , while South Africa has two indigenous social processes — indaba , which are part of Zulu culture in Kwazulu Natal, and imbizo or lekgotha in the Eastern Cape.…”
Section: Introductionmentioning
confidence: 99%
“…Schools already harness education as a tool to mitigate social issues faced by their students. The efficacy of prevention education to tackle negative social phenomena (e.g., addiction, suicide) has been well documented (Bonyani et al, 2018;Ghelani, 2010).…”
Section: Why Schools Should Be a Focus For Prevention And Interventionmentioning
confidence: 99%